1986
DOI: 10.1037/0022-0167.33.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Effects of role conflict on counselor trainees' self-statements, anxiety level, and performance.

Abstract: Counselor trainees play a dual role -subordinate in relation to their supervisors, superordinate in relation to their clients. The purpose of this study was to investigate if and how role conflict affects trainees' self-statements, anxiety level, and performance. A sample of graduate student counselors responded to a counseling dilemma and then were exposed to one of four experimental manipulations: conflict (the supervisor recommended action contradictory to the trainee's intended action), no conflict (the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
61
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 16 publications
2
61
0
Order By: Relevance
“…A negative relationship between anxiety and the strength of counseling selfefficacy expectations of the counselor-in-training was also documented (e.g., Bowman, Roberts, & Giesen, 1978;Bowman & Roberts, 1979;Friedlander, Keller, Peca-Baker, & Olk, 1986;Larson et al, 1992). Reising and Daniels (1983) found that pre-masters trainees report higher anxiety levels than masters level trainees.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…A negative relationship between anxiety and the strength of counseling selfefficacy expectations of the counselor-in-training was also documented (e.g., Bowman, Roberts, & Giesen, 1978;Bowman & Roberts, 1979;Friedlander, Keller, Peca-Baker, & Olk, 1986;Larson et al, 1992). Reising and Daniels (1983) found that pre-masters trainees report higher anxiety levels than masters level trainees.…”
Section: Introductionmentioning
confidence: 91%
“…The positive relationship between problem-solving appraisal and counseling self-efficacy was supported in previous studies (e.g., Larson et al, 1992). Likewise, anxiety was chosen because of its relationship to counseling self-efficacy as indicated in the literature (Friedlander et al, 1986;Larson et al, 1992;Thompson, 1986). In addition, practical observations indicate that psychology students at UAE university tend to exhibit high anxiety as they begin to learn the skills needed to practice psychological counseling.…”
Section: Introductionmentioning
confidence: 92%
“…Their participants reported feeling less competent and anxious during their clinical practicum (Friedlander et al, 1986 Conversely, participants in the negative supervisory experience group described their interactions with their supervisors as "uncomfortable". Many times, these participants perceived their supervisors as being "condescending" and "rude".…”
Section: Negative Supervisory Experiencesmentioning
confidence: 98%
“…Although it is recognized that clinical practicum is critical to the therapeutic effectiveness of supervisees, many students still report negative supervisory experiences (Barrett & Barber, 2005;Friedlander, Keller, Peca-Baker, & Olk, 1986;Gray, Ladany, Walker, & Ancis, 2001;Nelson & Friedlander, 2001). Research has demonstrated that negative supervisory experiences have a detrimental impact on supervisees (Friedlander et al, 1986;Gray et al, 2001;Nelson & Friedlander, 2001).…”
Section: Effects Of Negative Supervisory Experiencesmentioning
confidence: 99%
See 1 more Smart Citation